Pengembangan Media Flashcard untuk Meningkatkan Keterampilan Menulis Puisi Siswa Kelas VIII MTS Islamiyah Medan - Purnama Sari Siregar; Tri Indah Kusumawati; Budiman Budiman (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This development research aims to find out: (1) the process of developing flashcard media to improve students' poetry writing skills. (2) the feasibility of flashcard media in improving students' poetry writing skills. (3) The effectiveness of flashcard media in improving students' poetry writing skills.This research was conducted using the research and development model (R&D) (Research and Development) This research uses the ADDIE development model with five stages, namely analysis, design, development, implementation, and evaluation. The subjects in this study are MTs Islamiyah Medan students totaling 28 students. The instrument of this study is to use a questionnaire to see the development, feasibility and effectiveness of the media developed. Data analysis techniques use product data analysis, preliminary data analysis, hypothesis testing. The results of the study show that flashcard media for writing poetry is very feasible to use with an average percentage of media experts 81.25% and material experts 97.5%. There was an increase in the average student score of 80.17%, so it was concluded that the average pretest and pottest scores experienced significant changes. Research conclusion: flashcard media for writing student poetry is suitable for use in poetry material learning activities by grade VIII students of MTS Islamiyah Medan. Further research suggestion: more thorough in planning the development of flashcard media, it should be developed according to the needs and characteristics of students.